Three Faces of Fragile X. Issue 11 (1st November 2016) - Lieb-Lundell, Cornelia C.E.
Abstract: Fragile X syndrome (FXS) is the first of 3 syndromes identified as a health condition related to fragile X mental retardation ( FMR1 ) gene dysfunction. The other 2 syndromes are fragile X–associated primary ovarian insufficiency syndrome (FXPOI) and fragile X–associated tremor/ataxia syndrome (FXTAS), which together are referred to as fragile X–associated disorders (FXDs). Collectively, this group comprises the 3 faces of fragile X. Even though the 3 conditions share a common genetic defect, each one is a separate health condition that results in a variety of body function impairments such as motor delay, musculoskeletal issues related to low muscle tone, coordination limitations, ataxia, tremor, undefined muscle aches and pains, and, for FXTAS, a late-onset neurodegeneration. Although each FXD condition may benefit from physical therapy intervention, available evidence as to the efficacy of intervention appropriate to FXDs is lacking. This perspective article will discuss the genetic basis of FMR1 gene dysfunction and describe health conditions related to this mutation, which have a range of expressions within a family. Physical therapy concerns and possible assessment and intervention strategies will be introduced. Understanding the intergenerational effect of the FMR1 mutation with potential life-span expression is a key component to identifying and treating the health conditions related to this specific genetic condition.